African Lineage Brucella melitensis Isolates from Omani Livestock - Foster, Jeffrey T.; Walker, Faith M.; Rannals, Brandy D.; Hussain, M. Hammad; Drees, Kevin P.; Tiller, Rebekah V.; Hoffmaster, Alex R.; Al-Rawahi, Abdulmajeed; Keim, Paul; Saqib, Muhammad (Frontiers in Microbiology, 2018)
Brucellosis is a common livestock disease in the Middle East and North Africa, but remains poorly described in the region both genetically and epidemiologically. Traditionally found in goats and sheep, Brucella melitensis is increasingly recognized as infecting camels. Most studies of brucellosis in camels to date have focused on serological surveys, providing only limited understanding of the molecular epidemiology of circulating strains. We genotyped B. melitensis isolates from Omani camels using whole genome SNP assays and VNTRs to provide context for regional brucellosis cases. We identified a lineage of B. melitensis circulating in camels as well as in goats, sheep, and cattle in Oman, that is genetically distinct from most genotypes from the Arabian Peninsula and from isolates from much of the rest of the Middle East. We then developed diagnostic assays that rapidly identify strains from this lineage. In analyses of genotypes from throughout the region, Omani isolates were genetically most closely related to strains from brucellosis cases in humans and livestock in North Africa. Our findings suggest an African origin for B. melitensis in Oman that has likely occurred through the trade of infected livestock. Moreover, African lineages of B. melitensis appear to be undersampled and consequently are underrepresented in genetic databases for Brucella. As we begin to more fully understand global genomic diversity of B. melitensis, finding and characterizing these unique but widespread lineages is essential. We predict that increased sampling of humans and livestock in Africa will reveal little known diversity in this important zoonotic pathogen.